Hybrid forms: two “narrative” essays by Jorge Luis Borges - Rocha, Jéssica Aracelli (ITINERÁRIOS – Revue de Littérature, 2008)
This work analyses the hybrid narrative characteristics of two essays written by Jorge Luis Borges, “A Imortalidade” and “O Tempo”, included in his book Cinco Visões Pessoais. First of all, it examines the characteristics of hybridism in these texts and then it discusses their effects. It concludes by pointing out the different ways both texts break with the essay paradigm.